Detection of explosive vapors with a charge transfer molecule: self-assembly assisted morphology tuning and enhancement in sensing efficiency. - SCHMITT, WOLFGANG (My University, 2010)
Use of a fluorescent organic molecule consisting of binaphthyl functionalized with donor?acceptor substituted stilbenes for the detection of dinitrotoluene (DNT) and trinitrotoluene (TNT) vapors and enhancement in its sensing efficiency via self-assembly assisted morphology tuning are described.
PUBLISHED
Keywords: Chemistry